KONFLIK INTERNAL DPD PARTAI NASIONAL DEMOKRAT (NASDEM) KABUPATEN KUANTAN SINGINGI TAHUN 2015-2017 - Rendi Rinaldi; M. Y. Tiyas Tinov (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Nasdem Party is one of the twelve political parties that successfully pass the verificationand become the 2014 election participants. Nasdem Party in Kuantan Singingi regencybegan to form in 2013. The establishment of Nasdem Party in Kuantan Singingi regencycan not be separated from the struggle made by Sukasmi, H. Adnan Amir, and AlpianHamid. After Nasdem Party in Kuantan Singingi Regency was formed, Sukasmi wasappointed as chairman of DPD Party of Kuantan Singingi District Nasdem period2013-2018 and Secretary namely Zulfahmi Abdah. But in the middle of the road, inJune 2016, Sukasmi dismissed by DPW from the position of Chairman of DPD PartyNasdem period 2013-2018 and replaced by Sarjan as chairman of DPD Nasdem Partyin 2016. This dismissal is done because Sukasmi is considered by DPW can not carrymandate ideals the ideals of the Nasdem Party and unilaterally determining decisions.On the other hand, Sukasmi considered that the dismissal and removal was doneunilaterally and not in accordance with the mechanism of AD / ART Party Nasdem. Thisis because Sarjan new people join the Party Nasdem. The person who has the right tooccupy the position of chairman of the Party DPD Nasdem Kuantan Singingi namely:H. Adnan Amir, Alpian Hamid and Zulfahmi Abdah. Sarjan served as chairman of DPDParty Nasdem District Kuantan Singingi approximately one year and was replaced byMuslims in July 2017 for stewardship in 2017.Problem formulation in this research is "why the occurrence of internal conflictDPD Party Nasdem Kuantan Singingi Regency Year 2015-2017". The purpose of thisresearch is to describe internal conflict DPD Party Nasdem in Kuantan SingingiRegency Year 2015-2017.The results of this study indicate that internal conflict DPD Party NasdemKuantan Singingi 2015-2017 originated from differences in support of candidate pairbetween Sukasmi and Sarjan in elections of Kuantan Singingi district head, the processof determining the chairman of the DPD Party Nasdem District Kuantan Singingi not inaccordance with the mechanism of AD / ART, the difference of political interest betweenthe board of DPD Party Nasdem District Kuantan Singingi. This conflict belongs tosurface conflicts and latent conflicts.Keywords: Nasdem Party, Internal Conflict